Blog as a Media to Help First Grade of State Senior High School Students Write a Descriptive Text (RETAIN, 2016)
Blog as a Media to Help First Grade of State Senior High School Students Write a Descriptive Text Pratiwi Diashari English Education Department, Language and Arts Faculty, Surabaya State University Email: pratiwidiashari@mhs.unesa.ac.id Dra. Theresia Kumalarini, M.Pd English Education Department, Language and Arts Faculty, Surabaya State University Email: Theresiakumalarini@unesa.ac.id Abstract Since writing is considered to be the most difficult skill, it is necessary that teachers choose an appropriate media to attract the students improve their writing skill. One of the media which can used to attract the students is blog. Blog is one of the social media that still exists until recently. Using blog can motivate EFL learners to write eagerly. This research was done as a way to find out whether there is a significant difference in the writing ability on the participants after being taught by using blog. It has one group pre-test post-test design, the sample of which is 20 students of X MIA 3. In addition, the data are the scores of the participants’ pre-test and post-test which are analyzed using paired samples T-test. The result shows that their writing ability is better after being taught using Blog. There was a significant difference in terms of content, vocabulary, organization, and language use components, yet in mechanics component the difference was not significant. Keyword: Blog, Writing, Descriptive Text Abstrak Menulis merupakan salah satu aspek tersulit dalam pembelajaran sehingga sangatlah penting untuk guru memilih media yang tepat untuk menarik minat murid dalam meningkatkan kemampuan menulis mereka. Salah satu media yang dapat dipilih untuk menarik minat mereka ialah blog. Blog adalah salah satu sosial media yang tetap bertahan sampai saat ini. Penggunaan blog dapat mendorong keinginan siswa untuk menulis. Penelitian ini bertujuan untuk mengetahui apakah ada perubahan yang signifikan dalam kemampuan menulis siswa setelah diajar menggunakan blog. Penelitian ini menggunakan desain one group pre-test post-test, sampel dalam penelitian ini ialah 20 murid yang diambil dari kelas X MIA 3. Sebagai tambahan, data dalam penelitian ini diperoleh dari hasil pretest dan posttest dan dianalsis menggunakan paired samples T-test. Hasil menunjukkan bahwa kemampuan siswa menjadi lebih baik setelah pengaplikasian blog. Terdapat perbedaan yang signifikan dalam komponen konten, kosa kata, organisasi, dan pengunaan bahasa, sedangkan pada komponen mekanisme belum terlihat hasil yang signifikan. Kata Kunci: Blog, Menulis, Teks Deskriptif